Faculty Development Initiatives in Academic Dentistry: A Systematic Review. Issue 9 (1st September 2019) - Johnston, Chelsea; Ganas, Joyce; Jeong, Y. Natalie; Nevius, Amanda; Bassir, Seyed Hossein; Dragan, Irina F.
Abstract : The aims of this systematic review were to collect a list of published articles on dental faculty development and to determine the types and location of programs evaluated and years of publication. A subset of selected articles were then assessed using Kirkpatrick assessment model four levels: learner reaction, participant learning, participant behavioral change, and changes in organizational practice. The search, conducted in 2016, comprised all potentially relevant articles in the following databases: PubMed, EMBASE via Ovid, and ERIC. The study screening was done by three reviewers in multiple stages: by title, abstract, and full text review. Following deduplication, 257 titles were obtained; of those, 102 articles were selected for abstract review. As a result of that review, 32 articles were excluded, leaving 70 for data extraction. The majority of the 70 articles were about programs in the U.S., and two‐thirds were studies conducted at individual academic institutions. Most focused on faculty development initiatives (n=49), followed by retention (n=22), recruitment (n=16), and/or promotion/tenure (n=11). The year with the highest number of published articles was 1991 (n=10, 14%), followed by 2007 and 2011 (n=6, 8.6% each). Among the 12 articles evaluated with the Kirkpatrick model, most assessed Levels 1, 2, and 3, but very few addressed Level 4. Research in those 12 articles was conducted primarily at two dental schools: New York University College of Dentistry (n=5) and University of Florida College of Dentistry (n=4). This study generated a varied list of published articles on faculty development, but the results point to the need for research at more institutions and using additional methodologies.